Learning Curves in COVID-19: Student Strategies in the ‘New Normal’? - Millar, S-K; Spencer, K; Stewart, T; Dong, M (Frontiers Media SA, 2021)
In New Zealand, similar to the rest of the world, the COVID-19 pandemic brought unprecedented disruption to higher education, with a rapid transition to mass online teaching. The 1st year (and 1st semester in particular) of any University degree presents unique challenges for students. Literature suggests these students have significant learning concerns as they adjust to University teaching and assessment requirements. These challenges may be exacerbated with the rapid introduction of online learning environments as they are increasingly disconnected from their peers, and, at a greater risk of struggling with web-based learning technologies.
Keywords: Online bundle learning; Engagement; Higher education; COVID-19; Learning Management Systems